Entrepreneurship Among Minorities in Small Scale Industries: Literature Review and Research Perspectives - Pinto, Santhosh; Raghurama, A. (Prabandhan: Indian Journal of Management, 2010)
More than ever, the driving force in the modern economy remains entrepreneurship. Entrepreneurs are meeting our economic needs through the creation of thousands of new businesses each year. While larger corporations have instituted "downsizing" or "outsourcing" programs, job creation and economic growth has become the domain of the new ventures and the entrepreneurs who create them. If small businesses are to make the uttermost contribution to the economy, it is, therefore, incumbent on policy makers, trainers and business advisers to pay attention to the factors impeding and fostering their start-up.Small Scale Sector has been considered as one of the major contributors to economic development of India and the reasons are obvious. For a given quantum of capital, the employment potential offered by the Small Scale Industries is above two to three times more compared to large sector; also, for a given quantum of capital, greater economic activity can be sustained by setting up more units and the spread of units can be widely distributed to achieve decentralization of economic activity.